Global Development Finance 2008 (Complete Print Edition) - World Bank (Global Development Finance, 2008)
Global Development Finance-the World Bank's annual report on the external financing of developing countries-provides monitoring and analysis of development finance, identifying key emerging trends and policy challenges in international financial flows that are likely to affect the growth prospects of developing countries. As major financial institutions currently recognize losses from the U.S. subprime mortgage market crisis and rebuild their balance sheets through a more conservative approach to lending and risk management, the central theme of this year's report will be the market for international bank credit to developing countries.It is an indispensable resource for governments, economists, investors, financial consultants, academics, bankers, and the entire development community. Vol I: Analysis and Statistical Appendix reviews recent trends in financial flows to developing countries. Vol II. Summary and Country Tables* includes comprehensive data for 138 countries, as well as summary data for regions and income groups. Also available on CD-ROM, with more than 200 historical time series from 1970 to 2006, and country group estimates for 2007